2007
DOI: 10.1093/jac/dkm178
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of minocycline and colistin combinations on imipenem-resistant Acinetobacter baumannii clinical isolates

Abstract: The combination of colistin and minocycline was found to be bactericidal and synergistic against A. baumannii by time-kill methods. There was no agreement between time-kill and Etest methods for synergy testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 11 publications
4
60
0
1
Order By: Relevance
“…As it was previously mentioned, in heteroresistant isolates both COL-RIF and COL-IMI combinations were synergistic in inhibition of regrowth (Table 2). Similar findings were obtained with the colistinminocycline associations [17]. Few synergy studies have been conducted in A. baumannii COL resistant strains.…”
Section: Discussionsupporting
confidence: 83%
“…As it was previously mentioned, in heteroresistant isolates both COL-RIF and COL-IMI combinations were synergistic in inhibition of regrowth (Table 2). Similar findings were obtained with the colistinminocycline associations [17]. Few synergy studies have been conducted in A. baumannii COL resistant strains.…”
Section: Discussionsupporting
confidence: 83%
“…There are several reports in the literature of synergy studies performed with multidrug-resistant Acinetobacter baumannii (14,15,19). However, the synergy findings were not universal and may have been strain dependent (17), making it difficult to generalize the results.…”
Section: Discussionmentioning
confidence: 99%
“…There is some literature exploring combination antimicrobial therapy in the treatment of multidrug-resistant strains of Acinetobacter baumannii and Pseudomonas aeruginosa (8,14,15,17,19,21). However, there are limited data on combination therapy for KPC-producing K. pneumoniae.…”
mentioning
confidence: 99%
“…Numerous studies have been performed in recent years using a pharmacodynamic model or standard time-kill studies of the effect of polymyxin B or colistin against strains of P. aeruginosa (19,59,67,93,107,166), A. baumannii (60,88,106,136,160,170), and K. pneumoniae (20). Nearly all studies demonstrated that the polymyxins produce concentration-dependent killing, with an initial kill followed by regrowth.…”
Section: Bactericidal Activity and Synergy Studiesmentioning
confidence: 99%